Serological Detection of Nipah Virus in Domestic Animals in Malaysia Between 2012 and 2023 (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Malaysia experienced the Nipah virus outbreak in Negeri Sembilan, Perak, and Selangor from September 1998 to May 1999 and was granted Nipah-free status by World Organisation for Animal Health (WOAH) in 2001. In response to the severity of Nipah virus infections in both pigs and humans, the Department of Veterinary Services (DVS) Malaysia launched a Nationwide Surveillance Program designed to monitor pigs and domestic animals for the presence of the virus. Between 2012 and 2023, a total of 44,755 serum samples were received from cats (3,359), dogs (3,713), pigs (26,507), and horses (11,176) and tested using an in-house Indirect ELISA developed by the Veterinary Research Institute (VRI) of DVS Malaysia. No seropositive cases of Nipah virus IgG antibodies were detected in any of the tested samples. While this indicates that Malaysia has maintained its Nipah-free status, the absence of detectable antibodies does not eliminate the possibility of sporadic infections or the presence of the virus in other wildlife or animal reservoirs. This highlights the importance of ongoing surveillance efforts and emphasizes the need to understand zoonotic risks for both veterinary and public health in Malaysia.
Keywords: zoonotic surveillance; henipavirus; ELISA testing; veterinary diagnostic; public health risk